Strategy for Teaching Numerical Expressions through the Wordwall Platform for EJA Students - Santiago, Paulo Vitor da Silva; Santana, José Rogério; dos Santos, Maria José Costa (Journal of Instructional Mathematics, 2023)
This work is a pedagogical practice with students of Youth and Adult Education of a public school in Brazil with insertion of the basic operations of mathematics and numerical expressions. The objective of this research was to analyze the contributions of Gamification in meaningful learning based on the Theory of Didactic Situations with the contents of basic operations and numerical expressions with EJA high school students. The methodology at work is the qualitative approach with descriptive-exploratory objectives, applied to twenty-three EJA students, is composed of dynamic parts that occur simultaneously, following the stages of concept, structuring, application, development, resolution and conclusion of each student from the Didactic Contract and Didactic Transposition inserted in the concept of arithmetic and numerical expressions. Results show that gamification plays an important role in teaching mathematics learning inserted in the EJA high school class, which can be demonstrated at the time of the calculations described in the proposed activity. Finally, it is observed that the study carried out with Gamification and the students' discourse had a positive impact on the learning of all students, especially with regard to basic operations and numerical expressions.